An Analysis of Students’ Strategy In Learning Simple Past Tense At Tenth Grade of Senior High School 1 Jambi City - Martinus Jalu Andrian; Nurul Fitri; Kartika Dewi (JELT: Journal of English Language Teaching, 2022)
This study aims to find students' strategies in learning the simple past tense at tenth grade of Senior High School 1 Jambi City. In this study, this research used mixed methods and used an explanatory sequential research design. The total population of this research was the X MIPA of Senior High School 1 Jambi City. The sample was taken by using cluster sampling. The number of the sample were 36 students in class X MIPA 3. In collecting data, this research used questionnaires and interviews. The results of the study indicate that students in class X MIPA 3 are classified as medium in using language learning strategies with the average use of SILL is 3.15. Data analysis shows that students use all six of the categories of learning strategies; memory strategy, cognitive strategy, compensation strategy, metacognitive strategy, affective strategy, and social strategy. However, metacognitive strategy is the strategy most often used by students with an average use of 3.68 or classified in the high category. From the interview results, it is known that in studying the simple past tense, students apply language learning strategies which include memory strategy, cognitive strategy, compensation strategy, metacognitive strategy, affective strategy, and social strategy. However, of the six strategies, the memory strategy is the least used. Students apply these strategies in learning the simple past tense to help them overcome difficulties in learning the simple past tense and to better understand the use of the simple past tense orally and in writing.